MICROBIAL α-AMYLASES: STRUCTURE, FUNCTION AND APPLICATION – A REVIEW - B.N. SWARGIARI (International Journal of Pharma and Bio Sciences, 2015)
α-amylases are most important industrial enzyme and hold a major market share of enzyme sales. They hydrolyze starch molecules to small diverse products as dextrin and progressively smaller molecules of glucose units. α-amylases belong to the family 13(GH-13) of the glycoside hydrolase group of enzymes. Microbial α-amylases have a wide range of applications ranging from starch conversion to pharmaceutical applications. This article highlights on the characteristic features of α-amylase structure, function, family, primary microbial sources and uses of α-amylases in industrial purposes.